2020
DOI: 10.3126/ijssm.v7i4.32487
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and Resource Use Efficiency of Rice Production in Jhapa District of Nepal

Abstract: This research was conducted from January to June, 2020 to determine the profitability and resource use efficiency of rice production in Jhapa district of Nepal. The primary information was collected from 100 rice growing farmers, randomly selected from the sampling frame, using the pre-tested semi-structured interview schedule; moreover, two Key Informant Surveys were also done. In addition, the secondary information was collected from the review of related literatures. Descriptive statistics, Cobb-Douglas pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…Nearly the same pattern was found in the study of rice in Jhapa, reported the total cost of NRs.50, 901/ha. (Subedi et al, 2020), However, the production cost was found to be NRs 75,205/ha in rice farm in Morang (Pandit et al, 2020) and NRs.77,100/ha in Kapilvastu (Sapkota & Sapkota, 2019) which was higher than this survey findings. In addition, the variable cost occupied 79% of the total cost, whereas the fixed cost was 21% (Figure 1).…”
Section: Rice Seed Production Costcontrasting
confidence: 77%
See 1 more Smart Citation
“…Nearly the same pattern was found in the study of rice in Jhapa, reported the total cost of NRs.50, 901/ha. (Subedi et al, 2020), However, the production cost was found to be NRs 75,205/ha in rice farm in Morang (Pandit et al, 2020) and NRs.77,100/ha in Kapilvastu (Sapkota & Sapkota, 2019) which was higher than this survey findings. In addition, the variable cost occupied 79% of the total cost, whereas the fixed cost was 21% (Figure 1).…”
Section: Rice Seed Production Costcontrasting
confidence: 77%
“…The efficiency implies that inputs are allocated in the farm according to the market price (Shrestha et al, 2021). The inputs such as fertilizer, labor, and irrigation were the important factors, which affect the level of income (Subedi et al, 2020). The cost of key resources like labor, seed, and agrochemical impact on the efficiency of production to a large extent (Shrestha et al, 2021).In addition to it, farm mechanization has a positive influence to enhance the farm performance of rice growers (Vortia et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This implies that for every Naira (N1.0) invested in rice production, a profit of N1.7 was realized. Subedi, Yuga, Meena, Bimala, Jiban, & Bidya, (2020) and Ogechi, (2020) in their study on rice production in Nepal and in Nigeria respectively, had similar results and indicated the financial viability of rice production in their respective study areas.…”
Section: Costs and Returns To Rice Productionmentioning
confidence: 72%
“…Meena, Bimala, Jiban, & Bidya, (2020) from (xviii) to (xix) in which; = absolute value of percentage change in MVP of each resource, and r = efficiency ratio…”
mentioning
confidence: 99%
“…These findings emphasize the crucial importance of fertilizers. On the other hand, several other research did not believe that fertilizers did not affect crop yields, but in Malaysia, rice production has the same result as in developing countries (Subedi et al 2020).…”
Section: Production Elasticitymentioning
confidence: 91%